TORNERANNO I PRATI (2014), DE ERMANNO OLMI. EL ICONO Y LAS DECLARACIONES DEL AUTOR* - Dr. Fernando GONZÁLEZ GARCÍA (Fonseca, Journal of Communication, 2023)
According to its author, Torneranno i prati does not intend to be a realistic presentation of first world war events, but an icon, an object to reflect about. The movie was subsidized by the State and presented to the world as part of its commemorative activities. Olmi’s declarations through different media point nevertheless not so much to the sense of the movie as to the sense of those commemorations. Based on the concepts of text, paratext, intertextuality and indermediality, this paper aims to approach the sense of the movie as an artistic proposal, and to examine the relations it establishes with other works integrated in or mentioned by it. It also aims to contextualize those declarations that want to emphasize, as we propose here, the autonomy of the movie against an official speech.